PENGUATAN MEDIA LITERASI DAN MENGATASI KECANDUAN ANAK TERHADAP GADGET PADA ANAK-ANAK DI GAMPONG LANCANG GARAM - khalsiah, khalsiah; Yusuf, Muhammad; Afrillia, Yesy; Safriand, Safriand; Asrifan, Andi (MALLOMO: Journal of Community Service, 2023)
Background: The increase in knowledge about the internet is necessary for parents to keep up with the challenges of digital media and technology. The importance of strengthening media literacy is not limited to downloading ebooks but also printing them. Focusing solely on gadgets can limit thinking patterns, leading to a single direction. Purpose: The purpose of this aim is to: firstly, to promote media literacy and teach children how to use gadgets responsibly, and secondly, to explore the impact of devices on children's character. We aim to raise awareness about the potential dangers of social media and encourage the safe and thoughtful use of technology for childrenMethods The research method involves lectures, discussions, Q&A, and simulations of interacting with addicted children. Results The research findings demonstrate are the efficacy of using technologybased literacy media for learning through reading, exploring digital libraries, and visiting physical libraries. After observing and visiting digital libraries, as well as seeing library buildings in Lancang Garam village, Lhokseumawe City, it became clear that there are factors influencing children's interest in learning and reading (literacy). The biggest challenge facing children today is the unmonitored use of electronic media and various ICT platforms, as most parents and the surrounding environment do not provide sufficient supervision.Conclusion: Nowadays, technology is mainly represented by gadgets and smartphones, which people tend to rely on more than developing literacy skills in their daily routine. To ensure a healthy use of social media, it's essential to establish rules or guidelines from the beginning, which can help cultivate positive habits